2020
DOI: 10.1111/nyas.14299
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of learning and recognition of statistical regularities

Abstract: Statistical learning is a set of cognitive mechanisms allowing for extracting regularities from the environment and segmenting continuous sensory input into discrete units. The current study used functional magnetic resonance imaging (fMRI) (N = 25) in conjunction with an artificial language learning paradigm to provide new insight into the neural mechanisms of statistical learning, considering both the online process of extracting statistical regularities and the subsequent offline recognition of learned patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
5
12
0
Order By: Relevance
“…Consequently, it may be suggested that nonwords were rejected because they violated learnt statistical regularities, phantoms were endorsed based on statistical congruency with learnt regularities, while the higher acceptance rate for words than phantoms can be explained by the facilitatory effect of memory representations of whole triplets as words, presumably extracted and committed to memory as discrete constituents during the learning stage. This interpretation is in line with recent fMRI evidence (Ordin, Polyanskaya, & Soto, 2020a), where activation differences in the neural memory network were reported for presentation of both old and novel-but statistically congruent-triplets.…”
Section: Discussion (Experiments 1)supporting
confidence: 91%
“…Consequently, it may be suggested that nonwords were rejected because they violated learnt statistical regularities, phantoms were endorsed based on statistical congruency with learnt regularities, while the higher acceptance rate for words than phantoms can be explained by the facilitatory effect of memory representations of whole triplets as words, presumably extracted and committed to memory as discrete constituents during the learning stage. This interpretation is in line with recent fMRI evidence (Ordin, Polyanskaya, & Soto, 2020a), where activation differences in the neural memory network were reported for presentation of both old and novel-but statistically congruent-triplets.…”
Section: Discussion (Experiments 1)supporting
confidence: 91%
“…The mechanisms driving the neural response to regularity are poorly understood, but emerging work (Barascud et al, 2016;Auksztulewicz et al, 2017) has implicated an interplay between auditory cortical, inferior frontal and hippocampal sources in the discovery of regularity. A similar network has also been implicated in detecting more complex predictable structure (see Milne et al, 2018 for a summary and also Abla and Okanoya, 2008;Schapiro et al, 2012;Ordin et al, 2020).…”
Section: Predictability Of Deterministic Sequences Modulates Sustained Pupil Sizementioning
confidence: 99%
“…26,27 Such transitions, characterized by breaches in statistical structure, are likely to require adaptive behavioral responses. This adaptive cycle-in which detecting statistical violations between elements in sequences of events 28 affords optimal behavioral responseshas also honed the evolution of SL mechanisms, which were later redeployed for speech processing. In natural languages, TPs between syllables are often reset at the boundaries between linguistic constituents-words, phrases, and sentences.…”
Section: Introductionmentioning
confidence: 94%